2022
DOI: 10.3390/molecules27123697
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine–Immune Regulatory Network of Eucommia ulmoides Oliver

Abstract: Eucommia ulmoides Oliver (E. ulmoides) is a popular medicinal herb and health supplement in China, Japan, and Korea, and has a variety of pharmaceutical properties. The neuroendocrine–immune (NEI) network is crucial in maintaining homeostasis and physical or psychological functions at a holistic level, consistent with the regulatory theory of natural medicine. This review aims to systematically summarize the chemical compositions, biological roles, and pharmacological properties of E. ulmoides to build a bridg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 155 publications
0
5
0
Order By: Relevance
“…With in-depth studies, some flavonoids, including quercetin and kaempferol, have also been identified in PN. A study based on animal experiments showed that combining PNS with other notoginseng flavones increased its biological activity (42). This work provided valuable experimental evidence and clues for the design of anti-fatiguing compounds.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…With in-depth studies, some flavonoids, including quercetin and kaempferol, have also been identified in PN. A study based on animal experiments showed that combining PNS with other notoginseng flavones increased its biological activity (42). This work provided valuable experimental evidence and clues for the design of anti-fatiguing compounds.…”
Section: Discussionmentioning
confidence: 79%
“…Among these products, EUOB has the highest frequency and is often used as the main component of related products. Traditionally, EUOB is thought to be a major medicinal component for prevention and treatment of chronic diseases such as osteoporosis, arthritis, and hypertension (41)(42)(43). However, slow growth of trunk bark has limited the supply of EUOB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eucommia ulmoides Oliver (EU), also known as Du-Zhong in China and Tuchong in Japan, is a traditional medicinal plant that originated in China and is widely distributed in central and southwest China, including Henan, Hunan, Jiangxi, and Shanxi provinces [ 1 ]. The bark of E. ulmoides (EUB) has been used in traditional Chinese medicine for more than 2000 years.…”
Section: Introductionmentioning
confidence: 99%
“…Fitting drugs that promote callus growth while fixing broken bones is a common means of treating fractures in the clinic [5] . In traditional medicine, many Chinese herbs promote bone fracture healing, such as osteoclast supplementation, Eucommia ulmoides, and sequestration [6,7] . It is also commonly used in the clinic to treat fractures by prescription-containing osteoclast supplementation.…”
mentioning
confidence: 99%